L'oncial 0171, témoin-clef du développement du texte néotestamentaire avant le 3e s. : Un point sur Mt 10,17-32 - Pinchard, Laurent (Novum Testamentum, 2019)
This essay discusses the text of the 3rd c. uncial 0171. The uncial consists of three fragments, two pertaining to the text of Luke, and one pertaining to the text of Matthew (10: 17-32), which is the focus of the present study. Despite its extremely fragmentary nature, certain letters are sufficiently legible to permit a faithful reconstruction of the text. Although the "Western" character of the manuscript is well-established, some of the earlier studies of the textual variants seem to have overlooked or misinterpreted a number of key elements. Through a verse by verse reassessment of the textual variants in MS 0171, this study suggests some new explanations for their origins, and concludes that this is an important witness to the transmission of the text of the Greek New Testament.